Increasing Community Knowledge Through the Literacy Movement - Didiharyono D; Besse Qur'ani (To Maega : Jurnal Pengabdian Masyarakat, 2019)
Literacy is an important human skill that depends on the ability and awareness to continue learning. Literacy is very closely related to reading activities and information is interpreted as information or news about something. Information literacy in principle aims to develop skills in understanding the information needed or information literacy both through print media and online media. Community service activities will be carried out activities to increase community knowledge through literacy culture. The main problem experienced by the community in general is the low ability of people to read and get good and correct sources of information and avoid hoax information. The steps for the implementation of community service activities carried out in this community service are training activities, provision of useful books for the community, and assistance. The material presented in the training includes (a) the delivery of basic literacy skills in improving reading, writing, numeracy, science, communication information technology (ICT), financial, and cultural & citizenship skills; (b) information literacy through the introduction of electronic sources (technology), critical thinking, problem solving, communication and synthesis; (c) strategies for selecting correct information and stating the source accurately and avoiding hoax information or false information that contains defamation and blasphemy; and (d) motivation for students to have a sense of caring for the surrounding environment. The results of community service can be concluded that the increase in community knowledge through literacy culture is done through the delivery of training materials, the provision of books that are beneficial to the community, and mentoring activities. As a recommendations for further community service activities is focused on fostering students dropping out of school, dropping out of elementary school, dropping out of middle school, and dropping out of high school through literacy culture based on the identification of problems previously carried out.